Respuesta :

You need to add one equation to the other. To do this, multiply the divide the entire equation by 2. The resulting equation gives: -6x + 3y = 9
Now, add this to the second. Doing this will cancel out the 6xs because they are opposite signs.
-4y = 4 is your simplified equation. 
Solve for y: y = -1
Plug this into an original equation.
-12x + 6(-1) = 18
-12x -6 = 18
-12x = 24
x = -2
-12x+6y=18 First line up the two equations
6x-7y=-5
-12x+6y=18
12x-14y=-10 Then find common factor and multiply one of the variables.
-8y=8Next eliminate the x and solve for y by dividing -8 on both sides getting
y=-1
Lastly plug in y into one of the original equations and solve for x
Check your answer by plugging into the original equation

ACCESS MORE